2005
DOI: 10.1007/s00270-004-0039-z
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic Relationship of the InternalJugular Vein and the Common Carotid Artery Applied to Percutaneous Transjugular Procedures

Abstract: Knowledge of the IJV anatomy and relationship to the CCA is important information for the operator performing an IJV puncture, to potentially reduce the chance of laceration of the CCA and avoid placement of a large catheter within a critical artery, even when ultrasound guidance is used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(45 citation statements)
references
References 12 publications
1
41
0
3
Order By: Relevance
“…These rates were 4%, 16%, 71%, and 9% for the right IJV, respectively. In only one of the patients, IJV was found to be medial to the artery [15].…”
Section: Discussionmentioning
confidence: 95%
“…These rates were 4%, 16%, 71%, and 9% for the right IJV, respectively. In only one of the patients, IJV was found to be medial to the artery [15].…”
Section: Discussionmentioning
confidence: 95%
“…We were able to detect pre-existing thromboses, small diameter IJVs, and atypical IJV location. Anatomical variations in the position of the IJV have been shown in a high percentage of general population by ultrasound imaging [18,19]. It is not unusual that the IJV is partly or fully superficial to the carotid artery, which makes accidental arterial puncture a possible risk.…”
Section: Discussionmentioning
confidence: 99%
“…SR30 to the contralateral side resulted in anterior venal shift [2,3,6,8,[11][12][13][14][15][16]. These studies have shown that the IJV is commonly positioned lateral or anterolateral to the CCA, and the incidence of overlap was reported to be between 6 and 95%, depending on the method of calculation.…”
Section: Discussionmentioning
confidence: 96%
“…The classic Sedillot triangle, which is formed by external landmarks (the clavicle and both heads of the sternocleidomastoid), has been commonly used for IJV punctures for decades. Both this triangle and the relationship of the IJV to the common carotid artery (CCA) are well known, and this landmark-guided technique is performed on the assumption that the IJV is usually situated laterally to the CCA [1,2]. Although there is a high success rate (95%) when these landmarks are used [3], unexpected positional or anatomic variations of the CCA could result in inadvertent puncture of the CCA; this occurs in 3 to 10.6% of cases [4,5].…”
Section: Catheterization Of the Internal Jugular Vein (Ijv) Is Amentioning
confidence: 99%